Taurine-magnesium Coordination Compound Attenuates Hypoxia/Reoxygenation Induced Ion Channel Dysfunction in Rat Ventricular Myocytes - Zhao, L.; Lou, J.-S.; Kang, Y. (Drug Research, 2013)
Because of the known anti-arrhythmic effects of taurine-magnesium coordination compound (TMCC), the aim of the present study was to explore the electrophysiological effects of TMCC on hypoxia/reoxygenation (H/R)-induced arrhythmias in rat ventricular myocytes. Sodium current (INa), the L-type calcium current (ICa,L), and the transient outward potassium current (Ito) were evaluated using whole-cell patch-clamp recordings in rat ventricular myocytes following H/R injury. The H/R group significantly decreased sodium currents, while L-type calcium currents and transient outward potassium currents was significantly increased (all p<0.01). TMCC (200 and 400 μM) prevented abnormal sodium currents induced by H/R by inhibiting steady-state inactivation. It also counteracted abnormal L-type calcium currents induced by H/R by inhibiting steady-state activation and facilitating steady-state inactivation. In addition, it mitigated abnormal transient outward potassium currents induced by H/R by inhibiting steady-state activation. TMCC prevents H/R-induced arrhythmias in rat ventricular myocytes by modifying ion channel function.
Keywords: arrhythmia; ion channels; hypoxia/reoxygenation; rat; myocytes